DEVELOPMENT PERSPECTIVES OF RE-COMMERCE IN POLAND AND UKRAINE - Demianiuk, Regina; Levytska, Svitlana (Management and Administration Journal, 2025)
There is a growing interest in e-commerce channel among buyers and sellers in Poland and Ukraine. The aim of this article is to present the essence of reverse e-commerce and ensure better understanding of its development perspective in both Polish and Ukrainian electronic commerce. In Poland the development of reverse commerce is reflected in customer shopping behaviour and most transactions take place online. In Ukraine, we can see a growing interest in pre-owned trade on the Internet, as sellers and buyers discern the potential of online re-commerce essence in providing savings as well as additional income. As the entire e-commerce sector recovers to pre-martial law level in 2022 and continues to develop, the share of reverse commerce in online sales will be increasing. Electronic commerce in secondary circulation may be a good reaction to geopolitical, economic, social and ecological challenges, both in Poland and Ukraine. Re-commerce practices are beneficial for buyers, for the planet, future generations as well as for sellers. It is worth to implement them on a larger scale in the activities of economic entities on both sides of the border.